Mewujudkan Sustainable Development Goals: Implementasi Pengelolaan Lingkungan pada Perusahaan Pertambangan di Indonesia - Handayani, Nurma; Sari, Shinta Permata (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Achieving the Sustainable Development Goals (SDGs) requires support from business actors to address environmental degradation and climate change. This study aims to analyze the impact of SDG achievement influenced by Environmental Accounting, Material Flow Cost Accounting, Environmental Performance, and Environmental Cost in mining companies listed on the Indonesia Stock Exchange during the period of 2019–2023. The applied approach is quantitative, using purposive sampling, involving 70 companies as samples. Data processing was carried out using multiple linear regression methods. The findings of this study show that Environmental Accounting does not impact the SDGs, as its implementation remains formal and not fully integrated. In contrast, Material Flow Cost Accounting has an effect on the SDGs by improving resource efficiency and reducing waste. Environmental Performance impacts the SDGs, emphasizing the urgency of sustainable resource management and environmental protection. On the other hand, Environmental Cost does not influence the SDGs, indicating that the allocation of environmental costs by companies has not been optimally carried out. This research contributes to the development of the sustainability literature in the mining sector and encourages more effective environmental strategies. The practical implications of this study highlight the importance of implementing sustainability strategies to enhance corporate competitiveness and image, and it can serve as a basis for designing stricter regulations to promote environmentally friendly business practices and support the achievement of SDGs.